Zen Classics: Formative Texts in the History of Zen Buddhism, eds Steven Heine & Dale S. Wright - Kieschnick, John (Buddhist Studies Review, 2007)
Zen Classics: Formative Texts in the History of Zen Buddhism, eds Steven Heine & Dale S. Wright (Oxford: Oxford University Press, 2006), viii + 283 pp, £14.99, ISBN 0-19-517525-5